KH.M.'S Educational Concept Hasyim Asy'ari's Perspective on the Jihad of Ibn Qoyyim Al Jauziyyah - Abdul Hakim; Didin Saepudin; Adian Husaini (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the educational evaluations of KH. Hasyim Asy'ari in the context of jihad, as conceptualized by Ibn Qayyim al-Jawziyyah. The research focuses on four key aspects of evaluation: spiritual, intellectual, physical, and social, examining how these align with the broader concept of jihad. KH. Hasyim Asy'ari's holistic approach to education emphasizes the integration of spiritual, intellectual, physical, and social development to produce balanced individuals who can contribute to society and practice Islamic principles. Spiritual evaluation focuses on self-purification and closeness to Allah, intellectual evaluation emphasizes mastery of knowledge, physical evaluation highlights the importance of fitness and readiness, and social evaluation promotes contributions to the welfare of society. By aligning these educational goals with the concept of jihad, the study reveals how education serves as a powerful tool for character development, fostering a balance between spiritual growth and worldly responsibilities. The findings suggest that KH. Hasyim Asy'ari's educational model, deeply rooted in Islamic teachings, provides a comprehensive framework for preparing individuals to contribute both to their faith and society, encouraging continuous self-improvement and reflection.